2020
DOI: 10.3390/medicina56020077
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Soluble Urokinase-Type Plasminogen Activator Receptor in Obstructive Sleep Apnoea

Abstract: Background and Objectives: Obstructive sleep apnoea (OSA) is associated with heightened systemic inflammation and a hypercoagulation state. Soluble urokinase-type plasminogen activator receptor (suPAR) plays a role in fibrinolysis and systemic inflammation. However, suPAR has not been investigated in OSA. Materials and Methods: A total of 53 patients with OSA and 15 control volunteers participated in the study. Medical history was taken and in-hospital sleep studies were performed. Plasma suPAR levels were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…PAI1 is a pivotal player in the pathogenesis of sepsis, a complex clinical syndrome that results from a systemic inflammatory response. 11 The present study showed the mean age of the included patients was 62.1 ± 1 0.7 years and this agreed with the study by Mohamed et al, 12 who found (71.25%) of patients were males and (28.75%) were females. Maximum patients had belonged to the age group of 50-80 years of age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…PAI1 is a pivotal player in the pathogenesis of sepsis, a complex clinical syndrome that results from a systemic inflammatory response. 11 The present study showed the mean age of the included patients was 62.1 ± 1 0.7 years and this agreed with the study by Mohamed et al, 12 who found (71.25%) of patients were males and (28.75%) were females. Maximum patients had belonged to the age group of 50-80 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…PAI1 is a pivotal player in the pathogenesis of sepsis, a complex clinical syndrome that results from a systemic inflammatory response. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The latter was found to show decreased expression in OSA [ 103 ]. The soluble levels of uPAR were found unaltered in OSA [ 104 , 105 ]. The expression of uPAR is upregulated by proinflammatory cytokines [ 28 , 106 , 107 , 108 ] and TGF-β [ 109 , 110 ].…”
Section: Current Knowledge On the Effects Of Osa On Coagulation Fmentioning
confidence: 99%
“…The soluble urokinase type plasminogen activator receptor (suPAR) is a promising biomarker of cardiovascular disease [16]. However, Bocskei et al reported unaltered suPAR levels in OSA [17]. Despite the relationship between cardiovascular disease and OSA, little is known about the characteristics of obstructive sleep apnea in special subgroups of patients.…”
Section: Introductionmentioning
confidence: 99%